Challenges and opportunities for nurses during COVID-19 pandemic - Ambika Thapa Pachya; Uttam Pachya; Namuna Thapa; Rojina Tandukar; Jyotsna Singh Shrestha; Jeevan Thapa; Bandana Neupane; Madhusudan Subedi (Journal of Karnali Academy of Health Sciences, 2020)
Background: Pandemic of COVID-19 coincided with the year of Nurses and Midwives 2020. In war against invisible that has been ongoing during this pandemic, nurses play crucial role. As of June 2020, more than 600 nurses have lost their lives due to COVID-19. Nursing practice takes patients’ safety at paramount through continuum of testing, quarantine and isolation. Thus, there is need to review challenges that pandemic has posed as well as the avenues of opportunities that it has opened for nurses.